Issues and Challenges of Public Administration Education and Training in Nigeria - Okolie, Ugo Chuks; Okereka, Onofere Princewill (The Indonesian Journal of Social Studies, 2022)
superstructure and the indirect local administration system that was established in the 1900s and ended in 1960 when the nation won independence from Britain are used to track the history of public administration. Nigeria, a multiethnic country, has gone through a number of administrative and governmental reforms that have had a significant impact on the development of public Service and continue to present difficult challenges for academic institutions and other organizations tasked with public administration education and training. The development of public administration education and training in Nigeria is discussed in this article. The British The purpose of this study is to better understand the nature of public administration education and training in Nigeria using a qualitative research design. The claims made in this theoretical study were supported by secondary evidence taken from books, journal articles, and other publications. Multiple secondary sources were used in order to lower the likelihood of mistake and increase the study's reliability and validity. The study therefore make recommendations to enhance public administration education and training in Nigeria both now and in the future based on the knowledge gained through public service reforms and pedagogical techniques and methods.